PREFERENSI MAHASISWA UNIVERSITAS PGRI SEMARANG DALAM MENGERJAKAN TUGAS DI ARTIFICIAL INTELLIGENCES (AI) - Aviv Risqi Afani; Taufik Hidayat; Rauly Sijabat (SUAN PUBLISHER, 2025)
This study aims to analyze PGRI Semarang University students' preferences in using artificial intelligence (AI) to complete academic tasks. The background of this research focuses on the rapid development of technology, especially AI, which has become an important tool in the teaching and learning process. The research method used is qualitative with data collection techniques through interviews and questionnaires to students who are active users of AI. The results show that students feel significant benefits from using AI, such as increased efficiency in completing tasks and better understanding of the material. However, there are also challenges such as dependence on technology, potential plagiarism, and decreased creativity. This study concludes that although AI provides many advantages in education, it is important for students to use this technology wisely and still develop critical thinking skills and maintain academic integrity. Support from educational institutions is also needed to facilitate a better understanding of the use of AI in academic contexts.